INVESTIGATION OF THE ANTIOXIDANT CAPACITY OF THIOL-CONTAINING COMPOUNDS USING THE PHOTOCHEMILUMINESCENCE TECHNIQUE - Alin Dumitru Ciubotaru; Laura Stoica; Liliana Georgeta Foia; Vasilica Toma; Delia Lidia Salaru; Carmen-Ecaterina Leferman; Bogdan Alexandru Stoica; Cristina-Mihaela Ghiciuc (Romanian Society of Oral Rehabilitation, 2023)
Thiol-containing compounds, renowned as potent antioxidants, encompass various drugs and naturally occurring biological substances prevalent within the body. Aim of the study The study aimed to determine the level of inhibition of the photochemiluminescence reaction across therapeutic and physiological concentration ranges. Material and methods In order to quantify the in vitro antioxidant potential of these compounds photochemiluminescence technique was utilized. Eight bivalent sulfur compounds, predominantly derived from cysteine, were used: six with free SH groups (cysteine, homocysteine, N-acetyl-cysteine, captopril, glutathione, lipoic acid), one with a methylated SH group (methionine), and one with an oxidized SH group (cystine). Results After establishing a dynamic standard curve for UV-radiated oxidized luminol, the inhibitory effects of selected -SH containing compounds were investigated. It was observed that substances containing free SH groups diminished the intensity of light emission, contrasting with those containing blocked or oxidized thiols. The inhibition level appeared directly correlated with the antioxidant capacity of the compounds. Conclusions Glutathione demonstrated superior antioxidant activity across all tested concentrations.